Osama Bin Laden - Scheuer, Michael (Oxford University Press, 2011)
This book provides an objective and authoritative portrait of Bin Laden that will show him to be a man of remarkable leadership skills, strategic genius and considerable rhetorical abilities. For ten years, he has eluded capture despite being the most hunted man in the world.